Silent And Sinister Colon Cancer - Montserrat, Herrera Medina Jessica; Ávila, Juan Antonio Juárez; Martínez, Bertha Zenaida Acevedo; Barrón, Gema Méndez; Eugenio, Hugo Neftalí Bocanegra; Ramírez, Mario Rogelio Ortíz; Gómez, Jesús Ricardo Delgado; Pazos, Mauricio Israel Flores; García, Baruj Ricardo Lupio; Pineda, Nancy Mendoza; et al. (British Journal of Healthcare and Medical Research, 2024)
Introduction: colon and rectal cancer is unfortunately an emerging public health problem since it occupies second to third place worldwide in incidence, with a high mortality rate. Objective: presentation of a case and review of the literature. Method: 71-year-old male, who was evaluated in the emergency department, underwent an emergency surgical procedure due to a clinical picture suggestive of acute complicated and perforated appendicitis, performing exploratory laparotomy with extended right hemicolectomy. With a tumor that is an adenocarcinoma with areas of differentiation into signet ring cells. Discussion: The origin of colorectal cancer is complex and diverse, since it has a genetic origin, intrinsic factors, and extrinsic factors, which at some point combine or synergize. At the beginning it is completely asymptomatic, which explains the high incidence in advanced clinical stages and its lethality. The first-line treatment is resection or ablation, which ranges from colonoscopy as an initial option, to the same laparoscopic and/or robotic surgery, both multivisceral or the same pelvic exenteration. Conclusions: The symptoms and signs in colorectal cancer are not adequate for diagnosis and this causes late treatment with only repressive or palliative treatment, with a poor prognosis and obviously no survival.